Hypocretin and Melanin‐Concentrating Hormone in Patients with Huntington Disease - Aziz, Ahmad (Brain Pathol, 2008)
To evaluate whether hypocretin‐1 (orexin‐A) and melanin‐concentrating hormone (MCH) neurotransmission are affected in patients with Huntington disease (HD), we immunohistochemically stained hypocretin and MCH neurons and estimated their total numbers in the lateral hypothalamus of both HD patients and matched controls. In addition, hypocretin‐1 levels were determined in prefrontal cortical tissue and post‐mortem ventricular cerebrospinal fluid (CSF) using a radioimmunoassay. The total number of hypocretin‐1 neurons was significantly reduced by 30% in HD brains (P = 0.015), while the total number of MCH neurons was not significantly altered (P = 0.100). Levels of hypocretin‐1 were 33% lower in the prefrontal cortex of the HD patients (P = 0.025), but ventricular CSF levels were similar to the control values (P = 0.306). Neuronal intranuclear and cytoplasmic inclusions of mutant huntingtin were present in all HD hypothalami, although with a variable distribution across different hypothalamic structures. We found a specific reduction in hypocretin signaling in patients with HD as MCH cell number was not significantly affected. It remains to be shown whether the moderate decrease in hypocretin neurotransmission could contribute to clinical symptoms. As the number of MCH‐expressing neurons was not affected, alterations in MCH signaling are unlikely to have clinical effects in HD patients.